2019
DOI: 10.1186/s12883-019-1315-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warfarin versus aspirin on blood viscosity in cardioembolic stroke with atrial fibrillation: a prospective clinical trial

Abstract: Background Warfarin is evidence-based therapy for the prevention of cardioembolic stroke, but has not been studied for its effects on whole blood viscosity (WBV). This study investigated the effect of warfarin versus aspirin on WBV in patients presenting with non-valvular atrial fibrillation (NVAF) and acute cardioembolic stroke. Methods We enrolled patients with acute cerebral infarction, aged 56–90 years who had NVAF, CHADS 2 score ≥ 2, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…BV can be modified using drugs such as vasodilators, statins, or antithrombotics [2,16,17]. A few studies have examined the effect of antithrombotics on BV [17][18][19] and found that warfarin, heparin, and argatroban can decrease BV [17,20]. Varying results have been observed with antiplatelets, depending on the experimental protocol used in the study.…”
Section: Discussionmentioning
confidence: 99%
“…BV can be modified using drugs such as vasodilators, statins, or antithrombotics [2,16,17]. A few studies have examined the effect of antithrombotics on BV [17][18][19] and found that warfarin, heparin, and argatroban can decrease BV [17,20]. Varying results have been observed with antiplatelets, depending on the experimental protocol used in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to such variation in shear rate, the difference in WBV changes within 0.00175 Pa.s to 0.0055 Pa.s in average(0.5 ≤ ψ ≤ 1.5). On the other hand, in a prospective clinical trial, Lee et al 50 showed that Aspirin and Warfarin alter WBV by approximately 0.00042 Pa.s and 0.00024 Pa.s, for a shear-rate difference from 300 to 1000 s-1, respectively. Ma et al 51 found that Aspirin have noticeable effects on WBV at low shear rates (5 s-1) and negligible effects at medium and high shear rates (100 s-1, 200 s-1).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 32,33 have indicated that antiplatelet therapy will change the viscosity of blood, which is a crucial parameter when performing CFD simulation. The non-Newtonian blood viscosity model predict lower threshold of WSS values and slightly severe gradients.…”
Section: Discussionmentioning
confidence: 99%